INFEKSI HUMAN IMMUNODEFICIENCY VIRUS (HIV) PADA BAYI DAN ANAK - Johanis Johanis; Endang Retnowati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
HIV is an obligate intracellular RNA virus which fully replicates in the host cells notably express CD4+ receptor, such as CD4+ Tlymphocytes, astrocytes, microglias, monocyte-macrophages, Langerhans cells, dendritic cells. There are two types of HIV: HIV-1 and HIV-2. HIV-2 is less pathogenic and less contribution in children. In the developing countries the total number children with HIV increased higher than in the developed countries. HIV infection in children is more common in children who have HIV infected mothers, they are mostly transmitted during the laboring process. Breast milk from HIV infected mothers is a potential transmission media, there fore HIV infected mothers is not admitted giving breast milk to their babies. The risk factors of mother-child transmissions of HIV infection are: virus, maternal, obstetric, fetal and baby. Maternal HIV antibodies in child’s circulation cause the diagnosis of HIV in children difficult. There fore an accurate and fast diagnosis is needed to decrease the disease progressivity in children as well as by proper antiretroviral treatment. There are suggestion reference for diagnosis tests for HIV infection in babies and children <18 months by virology test using HIV-DNA PCR and HIV-RNA PCR. The diagnosis test for children ≥18 is HIV antibody test the same such as in adult. In HIV infected babies and children is used CD4+ T-lymphocytes percentage to monitor the disease progressivity.